Open In App
Related Articles

Quotient Rule | Formula, Proof and Examples

Improve
Improve
Improve
Like Article
Like
Save Article
Save
Report issue
Report

Quotient rule is a method used for differentiating problems where one function is divided by another. We use the quotient rule when we have to find the derivative of a function of the form: f(x)/g(x).

Let’s learn about the Quotient Rule in Calculus, its formula and derivation, with the help of solved examples.

Quotient Rule of Differentiation

Quotient Rule Definition

Quotient rule is the rule of differentiation of those functions that are given in the form of fractions, where both numerator and denominator are individual functions.

Suppose we are given a function f(x) = g(x)/h(x) then the differentiation of f(x), f'(x) is found as,

f'(x) = [g(x) × h'(x) – h(x) × g'(x)] / [h(x)]2

Quotient Rule Formula

The quotient rule formula is the formula used to find the differentiation of the function which is expressed as the quotient function. The quotient rule formula is,

d/dx [u(x)/v(x)] = [v(x) × u'(x) – u(x) × v'(x)] / [v(x)]2

Where,

  • u(x) is the first function which is a differentiable function, 
  • u'(x) is the derivative of function u(x), 
  • v(x) is the second function which is a differentiable function, and
  • v'(x) is the derivative of the function v(x).

Quotient Rule Proof

We can derive the quotient rule using the following methods:

  • Using Chain Rule
  • Using Implicit Differentiation
  • Using Derivative and Limit Properties

Now let’s learn about them in detail.

Derivation of Quotient Rule Using Chain Rule

To Prove: H'(x) = d/dx [f(x)/g(x)] = [f(x) × g'(x) – g(x) × h'(x)] / [g(x)]2

Given: H(x) = f(x)/g(x)

Proof:

H(x) = f(x)/g(x)

⇒ H(x) = f(x).g(x)-1

Using Product Rule,

H'(x) = f(x). d/dx [g(x)-1] + g(x)-1. f'(x)

Applying the power rule,

H'(x) = f(x). (-1)[g(x)-2.g'(x)] + g(x)-1. f'(x)

⇒ H'(x) = – [f(x).g'(x)] / g(x)2 + f'(x) / g(x)

H'(x) = [-f(x).g'(x)] + f'(x).g(x)] / g2(x)

Thus, the quotient rule is proved.

Read More:

Derivation of Quotient Rule Using Implicit Differentiation

Let’s take a differentiable function f(x), such that f(x) = u(x)/v(x).

u(x) = f(x).v(x)

using the product rule,

u'(x) = f'(x)⋅v(x) + f(x)v'(x)

Now solving for f'(x)

f'(x) = [u'(x) – f(x)v'(x)] / v(x)

Substituting the value of f(x) as, f(x) = u(x)/v(x)

f'(x) = {u'(x) – u(x)/v(x).[v'(x)]}/v(x)

f'(x) = {u'(x)v(x) – u(x).v'(x)} / v2(x)

Thus, the quotient rule is proved.

Read More On:

Derivation of Quotient Rule Using Derivative and Limit Properties

Let’s take a differentiable function f(x) such that f(x) = u(x)/v(x),

We know that,

f'(x) = limh→0 [f(x+h) – f(x)] / h

Substituting the value of f(x) = u(x)/v(x)

f'(x) = limh→0 [u(x+h)/v(x+h) – u(x)/v(x)] / h

f'(x) = limh→0 [u(x+h).v(x) – u(x).v(x+h)] / h.v(x).v(x+h)

Distributing the limit,

f'(x) = {limh→0 [u(x+h).v(x) – u(x).v(x+h)] / h}.{limh→0 1/v(x).v(x+h)}

⇒ f'(x) = {limh→0 [u(x+h).v(x) – u(x).v(x+h) + u(x)v(x) – u(x)v(x)] / h}.{ 1/v(x).v(x)}

⇒ f'(x) = {limh→0 [u(x+h).v(x) – u(x).v(x)] / h} {limh→0  [u(x)v(x+h) – u(x)v(x)] / h}.{ 1/v2(x)}

⇒ f'(x) = v(x){limh→0 [u(x+h) – u(x)] / h} -u(x) {limh→0  [-v(x+h) + v(x)] / h}.{ 1/v2(x)}

f'(x) = [v(x).u'(x) – u(x).v'(x)] / v2(x)

Which is the required quotient rule.

Read More On :

How to Use Quotient Rule in Differentiation?

To apply the quotient rule, we follow the following steps,

Step 1: Write the individual functions as u(x) and v(x).

Step 2: Find the derivative of the individual function u(x) and v(x), i.e. find u'(x) and v'(x). Now apply the quotient rule formula,

f'(x) = [u(x)/v(x)]’ = [u'(x) × v(x) – u(x) × v'(x)] / [v(x)]2

Step 3: Simplify the above equation and it gives the differentiation of f(x).

We can understand this concept with the help of an example.

Example: Find f'(x) if f(x) = 2x3/(x+2)

Given,

f(x) = 2x3/(x + 2)

Comparing with f(x) = u(x)/v(x), we get

  • u(x) = 2x3
  • v(x) = (x + 2)

Now Differentiating u(x) and v(x)

  • u'(x) = 6x2
  • v'(x) = 1

Using Quotient rule,

f'(x) = [v(x)u'(x) – u(x)v'(x)]/[v(x)]2

⇒ f'(x) = [(x+2)•6x2 – 2x3•1]/(x + 2)2

⇒ f'(x) = (6x3 + 12x2 – 2x3)/(x + 1)2

⇒ f'(x) = (4x3 + 12x2​​​​)/(x + 1)2

Product and Quotient Rule

The product rule of differentiation is used to find the differentiation of a function when the function is given as product of two function.

Product rule of differentiation states that , if P(x) = f(x).g(x)

P'(x) = f(x).g'(x) + f'(x).g(x)

Whereas the quotient rule of differentiation is used to differentiate a function that is represented as, division of two functions, i.e. f(x) = p(x)/q(x).

Then the derivation of f(x) using the quotient rule is calculated as,

f'(x) = {q(x).p'(x) – p(x).q'(x)}/q2(x)

Related Articles :

Quotient Rule Examples

Let’s solve some sample questions on the Quotient Rule.

Example 1: Differentiate \bold{y=\frac{x^3-x+2}{x^2+5}}          .

Solution:

Both Numerator and Denominator functions are differentiable.

Applying Quotient Rule,

y'=\frac {d}{dx}[\frac{x^3-5+2}{x^2+5}]

⇒ y'= \frac{[d/dx(x^3-x+2)(x^2+5)-(x^3-x+2)d/dx(x^2+5)]}{[x^2+5]^2}

⇒ y'= \frac{[(3x^2-1)(x^2+5)-(x^3-x+2)(2x)]}{[x^2+5]^2}\\=\frac{(3x^4+15x^2-x^2-5)-(2x^4-2x^2+4x)}{[x^2+5]^2}

⇒ y'= \frac{x^4+16x^2-4x-5}{[x^2+5]^2}

Example 2: Differentiate, f(x) = tan x.

Solution:

tan x is written as sinx/cosx, i.e.

tan x = (sin x) / (cos x)

Both Numerator and Denominator functions are differentiable.

Applying Quotient Rule,

f'(x)=\frac{(d/dx(sinx))(cosx)-(d/dx(cosx))(sinx)}{cos^2x}

⇒ f'(x)= \frac{cosx.cosx-(-sinx)(sinx)}{cos^x}

⇒ f'(x)=\frac{cos^2x+sin^2x}{cos^2x}

⇒ f'(x)=\frac{1}{cos^2x}

Example 3: Differentiate, f(x)= ex/x2

Solution:

Both Numerator and Denominator functions are differentiable.

Applying Quotient Rule,

f'(x)=[\frac{d/dx(e^x)(x^2)-d/dx(x^2)(e^x)}{x^4}]

⇒ f'(x)=\frac{e^x.x^2-2xe^x}{x^4}

Example 4: Differentiate, y=\frac{cosx}{x^2}

Solution:

Both Numerator and Denominator functions are differentiable.

Applying Quotient Rule,

y'=\frac{d/dx(cosx)(x^2)-d/dx(x^2)(cosx)}{x^4}

⇒ y'=\frac{-sinx(x^2)-(2x)(cosx)}{x^4}

⇒ y'=\frac{-(x^2)sinx-(2xcosx)}{x^4}

Example 5: Differentiate, f(p) = p+5/p+7

Solution:

Both Numerator and Denominator functions are differentiable.

Applying Quotient Rule,

f'(p)=d/dx[\frac{p+5}{p+7}]

⇒ f'(p)=[\frac{d/dx(p+5)(p+7)-d/dx(p+7)(p+5)}{(p+7)^2}]

⇒ f'(p)=[\frac{p+7-p-5}{(p+7)^2}]

⇒ f'(p)=[\frac{2}{(p+7)^2}]

Practice Problems

Here are a few practice problems on the Quotient Rule for you to solve.

P1. Find the derivative of f(x) = (x2 + 3)/(sin x)

P2. Find the derivative of f(x) = (2x2 + 3x + 5)/(x + 3)

P3. Find the derivative of f(x) = (x + 3)/(ln x)

P4. Find the derivative of f(x) = (x.sin x)/(x2)

Quotient Rule of Derivative- FAQs

1. What is Quotient Rule of differentiation?

Quotient rule of differentiation is the rule that is used to find the differentiation of the function which is given in the quotient form, i.e. a function given as the division of two functions.

2. What is Quotient Rule Formula?

Quotient Rule Formula is,

f'(x) = [u(x)/v(x)]’ = [u'(x) × v(x) – u(x) × v'(x)] / [v(x)]2

This formula gives the differentiation of the function that is represented as f(x)/g(x).

3. How to Derive the Formula of Quotient Rule?

Quotient rule can be derived using three methods,

  • By Derivative and Limit Properties
  • By Implicit Differentiation
  • By Chain Rule

4. How to Use Quotient Rule?

Quotient rule is used to find the differentiation of the function expressed as the division of two functions that includes, all the functions of form f(x) and g(x) such that individual differentiation of f(x) and g(x) exist and g(x) can never be zero.

5. How do you find the Derivative of a Division Function?

Derivative of the division function is easily found using the quotient rule formula, i.e. if we have to find the differentiation of H(x) such that H(x) is expressed as H(x) = f(x)/g(x) then its derivative is expressed as,

H'(x) = d/dx [f(x)/g(x)] = [f(x) × g'(x) – g(x) × h'(x)] / [g(x)]2

6. What is the Limit of Quotient Rule?

Quotient Rule for limits states that the limit of a quotient functions equals the quotient of the limit of each function.



Last Updated : 04 Jan, 2024
Like Article
Save Article
Previous
Next
Share your thoughts in the comments
Similar Reads